2022
DOI: 10.1097/icu.0000000000000836
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome and retinal diseases: an updated review

Abstract: Purpose of reviewThe gut microbiome, trillions of microorganisms residing in our digestive tract, is now believed to play a significant role in retinal diseases. Breakthroughs in computational biology and specialized animal models have allowed researchers not only to characterize microbes associated with retinal diseases, but also to provide early insights into the function of the microbiome in relation to biological processes in the retinal microenvironment. This review aims to provide an update on recent adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Studies on the interaction between the ocular and intestinal microbiota have increased in recent years. Some researchers hypothesize the existence of a gut-eye "axis": the alteration of the intestinal microbiota seems to be linked to some eye diseases, including uveitis, macular degeneration, and glaucoma [179][180][181][182]. Most microorganisms are located in the intestine, especially in the ascending colon: therefore, we can find bacteria, fungi, viruses, and helminths in constant symbiotic relationship with our immune system and with numerous functions, such as metabolic, protective, of immune education, and of vitamin production [183].…”
Section: Gut-eye Axismentioning
confidence: 99%
“…Studies on the interaction between the ocular and intestinal microbiota have increased in recent years. Some researchers hypothesize the existence of a gut-eye "axis": the alteration of the intestinal microbiota seems to be linked to some eye diseases, including uveitis, macular degeneration, and glaucoma [179][180][181][182]. Most microorganisms are located in the intestine, especially in the ascending colon: therefore, we can find bacteria, fungi, viruses, and helminths in constant symbiotic relationship with our immune system and with numerous functions, such as metabolic, protective, of immune education, and of vitamin production [183].…”
Section: Gut-eye Axismentioning
confidence: 99%
“…In addition, the gut (including intestinal microbiota and their products) could be mediators of liver-eye communication, as liver diseases regulate their homeostasis, which is intimately correlated with ocular pathogenesis [ 158 ]. It has been found that valeric acid, a gut microbiota metabolite, could penetrate to the eyes and sustain homeostasis of IOP, while NAFLD patients were less abundant in valerate [ 159 , 160 ].…”
Section: Molecular Pathways and Pathophysiological Regulationmentioning
confidence: 99%
“…The association of dysbiosis with ocular disorders such as uveitis, age-related macular degeneration, and choroidal neovascularization have been established, however the connection between gut dysbiosis and DR is still being elucidated. 53,60 Previous studies have investigated the mechanisms connecting the gut microbiome to the retina in diabetic patients, known as the “microbiota-retina axis.” 6164 This axis is believed to play an important role in retinal homeostasis and there is growing evidence that a diabetic-associated microbiome could lead to increased inflammation and vascular permeability, promoting the development of DR. 45 Moubayed et al found that Bacteroidetes were more abundant in the DR than in the DM and healthy control (HC) groups, suggesting that progression of retinal disease in T2DM may increase with higher composition of this phyla. 65 However, subsequent studies by Khan et al found that although the Bacteroidetes/Firmicutes (B/F) ratio was elevated in a univariate analysis, these results were not significant in a multivariate analysis when controlling for confounders such as age, gender, BMI, HbA1C, hypertension, cardiovascular disease, dyslipidemia, and diet.…”
Section: The Gut Microbiota In Diabetic Retinopathymentioning
confidence: 99%